Respuesta :
The standard form of a circle is:
(x-h)^2+(y-k)^2=r^2, where r=radius and (h,k) is the center of the circle.
We are told that r=6 and the center is (10,-6) so
(x-10)^2+(y+6)^2=36
(x-h)^2+(y-k)^2=r^2, where r=radius and (h,k) is the center of the circle.
We are told that r=6 and the center is (10,-6) so
(x-10)^2+(y+6)^2=36
Answer:- C. [tex](x-10)^2+(y+6)^2=36[/tex]
The standard equation for a circle is [tex](x-a)^2+(y-b)^2=r^2[/tex], where r is the radius and (a,b)= center of the circle such that a= abscissa and b= ordinate of center.
Given:- Center of circle=(10, –6) , radius r=6
Here abscissa of center a=10
ordinate of center b= -6
Substitute values of a, b and r in the standard equation of circle, we get
[tex](x-10)^2+(y-(-6))^2=6^2\\\Rightarrow(x-10)^2+(y+6)^2=36[/tex]
⇒ C is the correct answer.